The optimized development of China's service industry in the “Belt and Road” regional value chain: A social network analysis - Zhang, Hanmei (The American journal of economics and sociology, 2024)
The optimized development of service industry in the value chain can inject strong impetus into economic growth. The “Belt and Road” initiative provides a new path for China's service industry. This article combines value‐added accounting method and social network analysis method to study the network environment of service trade in the “Belt and Road” region and the individual characteristics of China's service trade. At the same time, the article deeply analyzes the factors that affect the optimized development of China's service industry in the “Belt and Road” regional value chain from the perspective of trade relations and puts forward countermeasures and suggestions accordingly. The study found that the “Belt and Road” regional service trade network has high density and shows a trend of blockization. As a core node in the regional service trade network, China has strong subjective initiative, connecting link, and independence in trade relations. Moreover, the optimization of China's service trade relations can further enhance its position in the “Belt and Road” regional value chain. At the same time, it can also enhance political and cultural identity, enhance China's discourse power, and promote the process of regional economic integration. Therefore, China's service industry can use the “Belt and Road” initiative to innovate the trade relationship model and realize the optimal development.